PROSEDUR PENGUJIAN SUBSTANTIF ATAS AKUN BEBANOPERASIONAL PADA PT DEF OLEH KAP JOACHIM ADHIPITER POLTAK DAN REKAN - Davin Akbar Ramadhan (2023)
In a company, it is necessary to assess the fairness or appropriateness of the financial statements produced by the procedures used through attestation services for evaluation with generally accepted accounting principles in Indonesia. In this case, the Public Accounting Firm Joachim Adhi Piter Poltak and Partners carried out an audit process for one of the clients, namely PT DEF with a substantive testing process as part of the planning and implementation reference during audit activities. One of the accounts that is part of the audited financial statements is operational expenses. operating expenses are costs used to support the company's business and production activities. From the audit steps carried out on expense accounts, it can be carried out such as analytical tests, materiality and vouching in the year being audited. The results obtained can be seen whether the audit assertions regarding operational expenses have been fulfilled and have been presented fairly in the financial statements.